2002
DOI: 10.1016/s0020-7292(01)00591-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of early cleavage embryo

Abstract: Early cleavage embryos possess greater implantation potential. Embryo transfer containing early cleavage embryos had a better clinical pregnancy rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…Early cleavage status is one of the most promising new parameters. In previous studies it was found that transferring embryos that had cleaved early led to a significantly higher pregnancy rate (Shoukir et al, 1997;Sakkas et al, 1998Sakkas et al, , 2001Bos-Mikich et al, 2001;Lundin et al, 2001;Fenwick et al, 2002;Tsai et al, 2002) and blastocyst development rate (Fenwick et al, 2002) as compared to non-early cleavage embryos. This is in accordance with the results obtained in the present study (46 versus 18% for pregnancy rate after SET, P , 0.001, and 66 versus 40% for blastocyst rate, P , 0.0001).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Early cleavage status is one of the most promising new parameters. In previous studies it was found that transferring embryos that had cleaved early led to a significantly higher pregnancy rate (Shoukir et al, 1997;Sakkas et al, 1998Sakkas et al, , 2001Bos-Mikich et al, 2001;Lundin et al, 2001;Fenwick et al, 2002;Tsai et al, 2002) and blastocyst development rate (Fenwick et al, 2002) as compared to non-early cleavage embryos. This is in accordance with the results obtained in the present study (46 versus 18% for pregnancy rate after SET, P , 0.001, and 66 versus 40% for blastocyst rate, P , 0.0001).…”
Section: Discussionmentioning
confidence: 98%
“…The morphological parameters for zygote quality include the number of nucleolar precursor bodies (NPB) and their distribution in the pronuclei (Scott et al, 2000;Tesarik et al, 2000;Wittemer et al, 2000). Early cleavage embryos were defined as those which had cleaved to the 2-cell stage 25-27 h after insemination or ICSI (Shoukir et al, 1997;Sakkas et al, 1998Sakkas et al, , 2001Bos-Mikich et al, 2001;Lundin et al, 2001;Fenwick et al, 2002;Tsai et al, 2002). The conclusion of all these studies was that transfer of early cleavage embryos leads to a higher pregnancy and implantation rate compared to the transfer of non-early cleavage embryos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the embryo status at 25 h did not predict affect the percentage of the fragmentation observed later [13]. Although many researchers have considered the connection between early cleavage and embryo morphology [5,12,[14][15][16][17], the early cleavage mechanism is still unknown. The first cell cycle seems to take place when the zygote prepares for the initial cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Ovulation induction was performed as reported previously (5). The embryos were transferred on day 3 after OCR.…”
Section: Methodsmentioning
confidence: 99%